Géographie et hydrologie de la ville de Reims/Durocortorum et de ses environs - Alain Devos; Claire Pichard; Gilles Fronteau; Sébastien Laratte (Gallia)
The main characteristics of Reims’ natural environment make it a plains city, lacking any major waterway, situated in a marginal position, between two sectors of low-lying plateaus. To the west, the territories formed by the Brie, the Soissonais and the Laonnois, are composed of Cenozoic (Tertiary) layers cut into by numerous deep valleys. These valleys provide the plateaus with significantly diversified environments, between the crops on the loess layers, forests generally along the clay covered interfluves, wetland meadows at the foot of the valleys, as well as multiple slopes with suitable exposure for vine cultivation. The Ile-de-France’s cuesta bounds these tertiary plateaus and dominates the much flatter chalky Champagne to the east, the Cretaceous (Mesozoic) chalk layers of which compose a much shallower topographical layout. These flatter landscapes facilitate the passage of overland throughways, but the poor soils, without irrigation or modification, remain useful only for pastoralism. The city is located within the breakthrough funnel of the Vesle, a small river native to the Champagne chalklands. This area, punctuated by mounds and foothills situated between two very different natural regions, provides Reims with a varied set of agricultural resources and diversified potential in terms of geomaterials. In addition to the geological and agricultural riches of the Reims plain, this article also details the hydrological framework of the city of Reims, whose historic center is located on the right bank of a small river, the Vesle, bordered by marshy and low-energy areas, in a relatively open environment. The historic heart of the city is located on the right bank of the river, atop an alluvial terrace that protects it from flooding, is responsible the flatness of the terrain and provides it with good access to groundwater (chalk vadose zone). The Vesle, which is about ten meters lower than the ancient city, is in fact a low-energy river, fed by aquifer drainage, with no significant runoff. Its primary bed is occupied by a vast marshy area rich in alkaline peat bogs, which borders the southern portion of the urban zone. The lack of surface runoff and the vulnerability to urban pollution pose a threat to the drinking water supply and wastewater disposal (low dilution) for an urban locality of this size.